IMPLEMENTATION OF UMKM FINANCIAL MANAGEMENT TO IMPROVE THE ECONOMY OF SIAK REGENCY - Nur Afni (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Micro, small, and medium enterprises (MSMEs) possess economic potential and serve as a source of income to meet the primary needs of economic actors. Moreover, MSMEs are independent businesses managed by local communities, creating a source of activity, thus contributing to regional economic development (Nugroho et al., 2020). The sustainability of MSMEs is not only ensured by profitable actors but also requires support from other parties such as the government, the private sector, banks and non-banks, and academics so that MSMEs can develop into better businesses and grow over time. The purpose of this study is to determine how to support MSMEs in managing company finances to improve the economy of the community in Siak Regency. However, not all MSMEs currently receive support based on the challenges they face, so MSME mentoring is a necessary program. This study uses a quantitative approach to observe the phenomenon and measure the business capacity of the community.